(untitled) (Journal of Parents and Teachers, 2014)
A coexistence plan requires to be adapted to the centre and to be real according to the characteristics of the school. What is important is not to create a plan but to improve coexistence. In this particular case, they identified a problem; they measured it and worked on the causes of this problem. They created a programme called “Viaja con la mente” (Travel with your mind), a mere game at the beginning, but then a programme to improve school coexistence which took into account difficult questions: team work, control between equals, positive reinforcement, disincentivation of non adequate behaviours, etc.